2016
DOI: 10.1016/j.kint.2016.07.018
|View full text |Cite
|
Sign up to set email alerts
|

The risk of chronic kidney disease and mortality are increased after community-acquired acute kidney injury

Abstract: We investigated whether community-acquired acute kidney injury encountered in a tertiary hospital emergency department setting increases the risk of chronic kidney disease (CKD) and mortality, and whether plasma biomarkers could improve the prediction of those adverse outcomes. In a prospective cohort study, we enrolled 616 patients at admission to the emergency department and followed them for a median of 62.1 months. Within this cohort 130 patients were adjudicated as having acute kidney injury, 159 transien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 37 publications
3
31
0
Order By: Relevance
“…In a large retrospective cohort, volume depletion was the most frequent etiology (58.5% of cases) for CA H -AKI with infection, either sepsis, urinary tract infection, or pneumonia, being present in over 40% of cases [6] . Another recent study revealed similar results with 38.5% of patients with CA H -AKI having sepsis compared to 24% without AKI [7] . Confounding infection with AKI results in poorer outcomes; in community-acquired pneumonia, the presence of CA H -AKI has been shown to increase the likelihood of mechanical ventilation, vasopressor support, and results in higher 30-day mortality increasing according to RIFLE class [8] .…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations
“…In a large retrospective cohort, volume depletion was the most frequent etiology (58.5% of cases) for CA H -AKI with infection, either sepsis, urinary tract infection, or pneumonia, being present in over 40% of cases [6] . Another recent study revealed similar results with 38.5% of patients with CA H -AKI having sepsis compared to 24% without AKI [7] . Confounding infection with AKI results in poorer outcomes; in community-acquired pneumonia, the presence of CA H -AKI has been shown to increase the likelihood of mechanical ventilation, vasopressor support, and results in higher 30-day mortality increasing according to RIFLE class [8] .…”
Section: Resultsmentioning
confidence: 52%
“…Talabani et al [5] reported 45% 3-year mortality for CA H -AKI compared to 15.7% ( p < 0.01) in the control cohort with similar figures reported at 5 years (44.6% in Soto et al [7] ). As expected the need for renal replacement therapy (RRT) is significantly higher for patients with CA H -AKI compared to non-AKI [7] .…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…This standardized approach has utility in epidemiological studies, for coding and billing purposes, and triggering electronic medical record alerts for ‘best practice’ guidelines; however, such an approach fails to account for the myriad clinical scenarios in which SCr is elevated due to incidental non-renal or even artefactual conditions, or as a normal physiologic response to a reduction in extracellular fluid volume (ECFV). In the majority of patients entering emergency departments or hospitals worldwide, any increase in SCr is often fleeting, and usually reversed within 72 h of fluid therapy, suggesting a depletion in ECFV as the primary culprit and a concomitant absence of intrinsic structural kidney injury 24 . More than a century of experimental and human studies have elucidated physiologic neurohormonal mechanisms that transiently decrease renal excretory function while conserving salt and water in ECFV depletion, resulting in the clinical condition classically denoted as ‘functional pre-renal AKI’ or even as ‘acute renal success’.…”
mentioning
confidence: 99%